2008
DOI: 10.1063/1.2905243
|View full text |Cite
|
Sign up to set email alerts
|

Combined optical and electrical modeling of polymer:fullerene bulk heterojunction solar cells

Abstract: Optical interference effects are important for the total absorption as well as the profile of the exciton generation rate in polymer:fullerene bulk heterojunction solar cells. For solar cells with an active layer of poly͓2-methoxy-5-͑3Ј ,7Ј-dimethyloctyloxy͒-1,4-phenylenevinylene͔ as electron donor and ͓6,6͔-phenyl C 61 butyric acid methyl ester as electron acceptor, the total exciton generation rate can be directly extracted from the saturated photocurrent. It is demonstrated that for solar cells with an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 26 publications
(34 reference statements)
0
89
0
Order By: Relevance
“…2 As a result, the saturated photocurrent is a direct measure for the amount of photons absorbed in the blend. 6 Typically, the dissociation efficiency in poly͓2-methoxy-5-͑3Ј ,7Ј-dimethoxyloctyloxy͒-p-phenylene vinylene͔ ͑MDMO-PPV͒ and ͓6,6͔-phenyl C 61 -butyric acid methyl ester ͑PCBM͒ bulk heterojunction ͑BHJ͒ solar cells is only 60% at short circuit conditions, representing a major loss mechanism in these devices. 2,7 …”
Section: Introductionmentioning
confidence: 99%
“…2 As a result, the saturated photocurrent is a direct measure for the amount of photons absorbed in the blend. 6 Typically, the dissociation efficiency in poly͓2-methoxy-5-͑3Ј ,7Ј-dimethoxyloctyloxy͒-p-phenylene vinylene͔ ͑MDMO-PPV͒ and ͓6,6͔-phenyl C 61 -butyric acid methyl ester ͑PCBM͒ bulk heterojunction ͑BHJ͒ solar cells is only 60% at short circuit conditions, representing a major loss mechanism in these devices. 2,7 …”
Section: Introductionmentioning
confidence: 99%
“…Note that Eq. ͑1͒ is often [6][7][8][9][10][11]14 written in the form p diss = k d / ͑k d + k f ͒, where the dissociation constant k d relates to k rec and 0 via k d = k rec n i 2 / 0 . However, using the form of Eq.…”
Section: Theorymentioning
confidence: 99%
“…This exciton then ͑ii͒ has to diffuse to the interface between the donor and acceptor molecules where it is separated. A frequently used model [6][7][8][9][10][11] for the simulation of current/voltage curves of organic bulk heterojunction solar cells assumes that the dissociated exciton ͑iii͒ first creates a charge transfer state 12,13 at the interface, before ͑iv͒ the electron and hole are separated and ͑v͒ transported to their respective junctions. A feature very uncommon to the classical picture of inorganic solar cells results from the interplay between electric field dependent dissociation and nonradiative recombination of the charge transfer state as outlined in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In a later stage we extended this model to a combined optical and electrical model. 12 The combined optical and electrical calculations confirmed that the exact shape of the absorption profile in the solar cells is not very critical as long as the active layer thickness ͑ALT͒ does not exceed 250 nm. 12 As a result the estimation of a maximum efficiency of 11% for a single cell, done with a constant profile, is expected to be approximately correct.…”
mentioning
confidence: 74%